Artificial Intelligence Applications and Innovations 11th IFIP WG 12.5 International Conference, AIAI 2015, Bayonne, France, September 14-17, 2015, Proceedings - Chbeir, Richard; Manolopoulos, Yannis; Maglogiannis, Ilias; Alhajj, Reda (IFIP Advances in Information and Communication Technology, 2015)
This book constitutes the refereed proceedings of the 11th IFIP WG 12.5 International Conference on Artificial Intelligence Applications and Innovations, AIAI 2015, held in Bayonne, France, in September 2015. The 35 revised full papers presented were carefully reviewed and selected from 81 submissions. The papers feature highly novel research describing innovative algorithms, systems, tools and techniques, as well as proposing advanced prototypes in the area of artificial intelligence.